Breast reconstruction using the profunda artery perforator (PAP) flap: Technical refinements and evolution, outcomes, and patient satisfaction based on 116 consecutive flaps. Issue 5 (May 2022) - Atzeni, Matteo; Salzillo, Rosa; Haywood, Richard; Persichetti, Paolo; Figus, Andrea
Summary: Introduction: When a deep inferior epigastric artery flap is not suitable, the profunda artery perforator (PAP) flap can be a good alternative for autologous breast reconstruction. Popularity of the PAP flap is expanding, but it is still only slowly being adopted worldwide. We report our experience with 116 consecutive PAP flaps showing refinements and evolution of the technique towards improvement in outcomes and patients' satisfaction. Methods: We prospectively collected data from consecutive PAP flap breast reconstructions performed from 2016 to 2019. Patients' demographics, pre-, intra-, postoperative data, and revision procedures were analyzed. The BREAST-Q and a specific questionnaire investigating outcomes at the donor site were completed preoperatively and 12 months postoperatively. Results: One-hundred and sixteen PAP flaps were performed in 86 patients, 64 unilateral and 22 bilateral breast reconstructions. Mean body mass index was 24.72 kg/m 2 (range 18.9–29.2) and mean flap weight was 251.30 g (range 152–455 g). Complications included donor site hematoma (1.7%), seroma (2.6%), fat necrosis (1.7%), and wound dehiscence (2.6%). No arterial/venous thrombosis nor flap losses were recorded. Patients reported high satisfaction in all BREAST-Q domains, with mean postoperative scores being higher than preoperative ones, suggesting a positive effect in quality of life and satisfaction. Scores were significant in the satisfaction with breast domain ( p  = 0.0016). Conclusions: Breast reconstruction with PAP flap yields a high success, low complications, and excellent cosmetic outcomes in the breast and donor sites. It improves patients' satisfaction and quality of life; hence, it can be considered an excellent option for autologous breast reconstruction.